Kształtowanie państwowości macedońskiej w jugosłowiańskim systemie federacyjnym w latach 1944-1991 - Dziewiałtowski-Gintowt, Bartosz (My University, 2010)
Przedmiotem pracy jest przedstawienie procesów społeczno-politycznych, towarzyszących kształtowaniu się i funkcjonowaniu Socjalistycznej Republiki Macedonii w federacyjnej Jugosławii w latach 1944-1991. W opinii niektórych historyków macedońskich stworzenie w sensie prawno-terytorialnym organizmu, znajdującego się w ramach federacji jugosłowiańskiej, mającego reprezentować prawa ludności macedońskiej, było równoznaczne z ustanowieniem zrębów państwowości macedońskiej. Zasadniczym problemem badawczym było ustalenie, czy w warunkach ustroju komunistycznego możliwa była faktyczna realizacja praw, które zostały przypisane Macedonii. W tym celu przedstawiono zmiany demograficzne i polityczno-ustrojowe w tej republice, te ostatnie na tle przekształceń jugosłowiańskiego systemu federalnego. Przedstawiono też działania emancypacyjne, podejmowane przez część macedońskich elit politycznych i intelektualnych z partii rządzącej oraz środowisk niekomunistycznych, zwłaszcza w pierwszych kilku latach omawianego okresu, kiedy były one najsilniejsze. Kolejnymi ważnymi z punktu widzenia tematu pracy zagadnieniami były kwestie statusu najliczniejszej mniejszości narodowej, a mianowicie Albańczyków w Macedonii, ocena polityki zmierzającej do integracji Albańczyków ze społecznością macedońską a także problem walki macedońskiej hierarchii prawosławnej o niezależność własnej organizacji kościelnej.Ramy chronologiczne pracy obejmują lata 1944-1991. Początek państwowości macedońskiej datuje się od zwołanej na dzień 2 sierpnia 1944 r. I sesji Antyfaszystowskiej Rady Wyzwolenia Narodowego Macedonii, kiedy zadecydowano o wejściu Macedonii w skład federacji jugosłowiańskiej. Wydarzenie to stanowiło wypełnienie postanowień II sesji Antyfaszystowskiej Rady Wyzwolenia Narodowego Jugosławii odbytej w dniach 29-30 listopada 1943 r. w Jajce. Wówczas to postanowiono o zorganizowaniu po wojnie federacyjnej Jugosławii, złożonej z sześciu republik, w tym Macedonii, a językowi macedońskiemu przyznano status równoprawny z językami serbskim, chorwackim i słoweńskim. Republika stała się tym samym równoprawnym i niezależnym członkiem związku narodów jugosłowiańskich – Federacyjnej Ludowej Republiki Jugosławii. Niezależność ta była jednak w sposób obiektywny ograniczona istnieniem federacji. Dlatego też data ta stanowi cezurę początkową pracy. Natomiast datą końcową pracy jest dzień 20 listopada 1991 r., w którym uchwalona została konstytucja niepodległej Macedonii.Praca składa się z sześciu rozdziałów. Rozdział pierwszy obejmuje koncepcje rozwiązania problemu macedońskiego w ostatniej ćwierci XIX i pierwszej połowie XX wieku. W związku z tym ma ona charakter wprowadzający do zasadniczego tematu rozprawy. Drugi rozdział poświęcono kształtowaniu się terytorium państwowego Macedonii w ramach federacji jugosłowiańskiej. W trzecim przedstawiono kwestie związane z rozwojem demograficznym i zmianami stosunków ludnościowych w państwie macedońskim w tym okresie, a także problemy narodowościowe i proces urbanizacji. Szczególne dużo miejsca autor poświęcił problemowi albańskiemu z uwagi na wysoki przyrost naturalny, największą spośród wszystkich grup narodowych aktywność w wewnętrznym ruchu migracyjnym oraz datującą się od lat siedemdziesiątych szczególną aktywność separatystyczną społeczności albańskiej. Czwarty rozdział obejmuje przekształcenia polityczno-ustrojowe w Macedonii na tle podobnych zjawisk w skali całej federacji. W tym celu przedstawiono m.in. zmiany ustrojowe w Jugosławii w latach 1944-1991 i ich wpływ na strukturę władzy w Macedonii. W piątym rozdziale przedstawiono, uwieńczone powodzeniem, zabiegi macedońskiej hierarchii prawosławnej na rzecz utworzenia niezależnej organizacji kościelnej. Ostatni rozdział obejmuje rozwój kultury, sztuki i oświaty w Macedonii, które mogły być propagowane w skodyfikowanym po II wojnie światowej języku macedońskim. Zarówno rozwój oświaty i kultury, jak i uzyskanie autokefaliczności Macedońskiej Cerkwi Prawosławnej w istotny sposób wpłynęły na pogłębienie procesu utożsamiania się Macedończyków z państwem.

The principal research problem of the dissertation is settlement of a real place of the Macedonian republic in the Yugoslav federation. The starting point should be drafting of demographic, political, constitutional, cultural and economic processes that occured in Macedonia on the background of similar phenomena in the united state. Fundamental is presentation of the level of dependence of the republic from federation, which were changing together with transformation of the Yugoslav federalism concept. In this context one should look at the attempts of emancipation of the Macedonian elites inside-party and outside-party from the federal centre shortly after the war. Next task will be to outline the problem of the national status of the Albanian minority in Macedonia and attempts of integration of these people with the Macedonian society. Besides, the author will make an attempt to answer the question: what was the range of freedom of strategic and economic decisions made by the communist rulers from Skopje. Chronological frameworks of the dissertation cover years from 1944 to 1991. The beginning of the Macedonian republic is dated on August 2nd 1944, on the first session of the Anti-Fascist Assembly for the People’s Liberation of Macedonia, when the state’s entry into Yugoslav federation was decided. Thereby Macedonia became a possesing equal rights and formaly independent member of the union of the Yugoslav nations – Federal People’s Republic of Yugoslavia. That’s why this day is a turning point and the beginning of presented work. On the other hand, the final event is November the 20th 1991, when Macedonian parliament adopted a new constitution, according of which Republic of Macedonia left the federation and thus became de iure and de facto an independent state. The dissertation is divided into six parts. First part contains all attempts of solution the Macedonian problem in the last quarter of XIX and first half of XX century. That’s why it has an entry form to the principal subject of the dissertation. In this chapter the author wants to concentrate on the projects of the authonomy for Macedonia whether in the frames of the Ottoman Empire or in the frames of the South-Slavs Federation and finally as a member of a broader union of the Balkan states. The proposals were advanced by the Great Powers or by the Balkan states competing with each other over this area or by the local educated inhabitants, united with aversion to the ottoman administration. In this part the author is concentrated basically on the activity on the last of these groups, which is pointed to prove that before the estabishment of the Macedonian republic (1944), the inhabitants of the Macedonian province many times were initiating an attempts of creation more or less independent form of Macedonian statehood. Because sometimes a state ideas on Macedonian lands were inspired and supported by the Balkan states, it might be motivated to outline the proposals made by Bulgaria and Serbia as well, but only in the range necessary to present their influence on the situation of slavic people in Macedonia. The second part describes the actions of the anti-communist opposition, Albanian problem, establishment of the Macedonian Orthodox Church and cultural, educational development of the state. In the relevance it is necessary to analise the Macedonian national idea, which in the author’s opinion, did not develop in the extent similar to other nationalisms in the federal Yugoslavia, limited by the constant pressure of the Serbian, Bulgarian and Greek claims. Part of Macedonian national idea was the language afirmation, codified as late as in 1945, which was a significant element formating Macedonian national identity. Another factor influencing the national status of Macedonians was numerous Albanian minority, its dynamic development in the socialist Yugoslavia, its attitude towards Macedonian people and a level of identification with Macedonian state. Another issue described in this chapter is the impact of education and culture on formation of civic identity of Macedonians. Distinct attention will be paid to the cultural role of the self-government institutions, which were acting on the republican level. It referred policy conducted towards artists, as well as organizing cultural life concentrated on the revival and cultivation of national traditions. Next crucial point is an origin and formation of Macedonian Orthodox Church in Yugoslavia as an important factor of culture-making, as well as state-making. An important question is the evolution of the authority system and costitution of Macedonia on the background of the federation. Political and law aspects of the form of Macedonian statehood will be presented through relations between the followers of the centralism and federalism idea in the Union of Macedonian Communist structure. Next question in this part is an evolution of the position of so-called Macedonian “liberals” towards constitutional system of socialist Macedonia. At the end were presented demographic and social changes that occured in the state during the described period. Based on the statistic data about migration movements, changes in the employment structure and in the urbanisation processes on the Macedonian area, will be presented social background which conditioned following phases of Macedonian state formation in 1944-1991.All the above together motivated the author to make an attempt to write a dissertation about the formation of Macedonian statehood to fill the blank in Polish historiography concerning this problem. The author has decided that a year of 1991 will be a final ceasure of his work, because of the creation of a new political and constitutional organism in this year, which was the Republic of Macedonia. This fact was the beginning of a new period in the newest history of Macedonia, which is not yet finished. That is why it seems to be right to finish the discurse about the transformation of Macedonia on the beginning of last decade of XX century.
The formation of Macedonian statehood in Yugoslav federal system 1944-1991
Wydział Historyczny: Instytut Historii: Zakład Bałkanistyki
Keywords: Państwowość; Statehood; Jugosławia; Yugoslavia; Macedonia